Sistema integrado de gestión administrativa como herramienta efectiva de toma de decisiones financieras en la Municipalidad Distrital de Huanchaco – 2017 - Huayunga Pizuri, Dimas Segundo (2019)
This thesis is about demonstrating the effectiveness of the Integrated Administrative Management System (SIGA) and as an effective tool in the entity's financial decision making. The problematic reality is summarized in the following question: To what extent is the Integrated Administrative Management System effective in making financial decisions of the District Municipality of Huanchaco - 2017? This is common in public entities, with the hypothesis “The Integrated System of Administrative Management is an effective tool in the financial decision making of the District Municipality of Huanchaco - 2017”. The result is adequate control in the efficiency of public spending, facilitating the authority, officials and servers that make up the District Municipality of Huanchaco to give it an appropriate and interpretive use of this administrative tool. The type of Investigation is Non-Experimental of Cross Section, and the deductive method was used. The population was composed of officials and specialists of the subject, with a sample of 60 people. The type of sampling applied is Intentional or Convenient. The techniques used for data collection were surveys, documentary analysis and interview. The instrument used was the questionnaire. The following information analysis techniques were applied: documentary analysis, survey, data reconciliation, tabulation, understanding of graphics. The following data processing techniques were applied: sorting and classification, manual registration, computerized process with Excel and computerized process with SPSS.